Inovasi Media Sosial dan Kelangsungan Usaha Mikro, Kecil, dan Menengah: Peran Kritis Literasi Digital - Maitri, Wayan Sri; Putra P, Komang Widhya Sedana; Laksmi P, Kadek Wulandari; Sukarnasih, Desak Made (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study is to analyze the effects of social media innovation on the business sustainability of MSMEs, taking digital literacy as a moderating variable. This research was conducted in Bali Province using a quantitative approach with data sources sampled from owners of MSMEs. A structured questionnaire was used. The data analysis used PLS-SEM, a technique of robust statistics that is appropriate for studying a complex relationship between variables. The research findings indicated that social media innovation significantly contributed to the sustainability of businesses within the MSME sector. It means that when MSMEs adopt and implement innovative social media strategies effectively, it leads to their overall sustainability and hence improves business outcomes. In fact, it was established in this study that the relationship can be moderated by digital literacy, meaning that MSMEs with higher levels of digital literacy are better positioned to leverage social media innovation for increased business sustainability. The results raise the need to incorporate social media innovation with digital literacy to promote sustainable practices among MSMEs. In doing this, businesses can keep up with the rapidly changing landscape of new technologies in ways that improve their competitive advantage. The paper, therefore, concludes with managerial implications: Owners of MSMEs need targeted training and resources to improve their digital literacy level so as to fully tap into the potential of social media innovations toward long-term sustainability.